Costos de transacción y creación de empresas: Una revisión de literatura (2008)
This article seeks to develop a theoretical comparison between the micro and macroanalytical approaches of Institutional Economics, keeping focus on the application of transaction costs that are commonly used in the studies on enterprise creation. In order to do this, the article reviews the works of Coase (1937, 1960, 1994), Williamson (1981, 1991) and North (1990, 1993), contrasting their analytical proposals on some articles published on that issue in order to find out if it would be useful to apply the cost transaction theory to the enterprise creation studies.